Note sur la théorie néo-keynésienne du producteur - Allard, Marie; Bronsard, Camille; McDougall, Gilles (L'Actualité économique)

(untitled) (HEC Montréal, 1981)
ABSTRACTWhile the meaningful theorems of neo-classical theory of the producer are well known, the neo-keynesian counterparts are not. Therefore, this paper will present those new meaningful theorems and their relations with neo-classical theory. On the one hand, this paper is of interest to the theoretician who would want to use the properties of comparative statics of the producer with quantitative rationing. On the other hand, since a neo-keynesian structural form is presented, the econometrician will be interested in imposing the meaningful theorems of this theory as a priori restrictions.